PENGEMBANGAN ENTREPRENEURSHIP BAGI UMKM KAWASAN AGROPOLITAN MELALUI PELATIHAN DAN PEMBUATAN PRODUK OLAHAN BERBASIS JAGUNG PULUT DI DESA MULYONEGORO, KECAMATAN PULUBALA, KABUPATEN GORONTALO - Sandalayuk, Marselia; Junus, Dikson; Puspaningrum, Dian; Ernikawati, Ernikawati; Hatta, Herman; Hidayat, Andi Sahrul; Marada, Nurhayati; Ishak, Olfin; Ngabito, Meriyanti; Sandalayuk, Daud; Dumbela, Adam Muhajrin; Mamula, Aldi Irfan; Talib, Ahmad Julianto; Pulukadang, Ariani; Bango, Dea; Mako, Sri Rahayu; Anggriani, Dwi; Tondako, Inka Noverita; Lapapang, Nurlita; Bina, Siti Nur Fadillah T. (Universitas Gorontalo, 2026)
Glut corn is a local commodity with significant potential for development as a value-added food ingredient. However, limited product innovation, technical skills, and marketing strategies remain major challenges for Micro, Small, and Medium Enterprises (MSMEs) in Mulonegoro Village, Pulubala District, Gorontalo Regency. This community service activity aims to describe the implementation of training in the production of glutinous corn-based processed products and assess its impact on increasing the capacity of MSMEs. The method used was a qualitative participatory approach through preparation, entrepreneurship training, and practice. Participants produced product innovations in the form of glutinous corn sticks, and demonstrated readiness to market their products independently. These findings confirm that local potential-based training can strengthen MSME motivation, increase product competitiveness, and open opportunities for village economic development. In conclusion, utilizing glutinous corn through diversified processed products not only supports the sustainability of MSMEs but can also be a strategy for economic empowerment based on local wisdom. Further research is recommended to explore digital marketing strategies and partnership models that can expand the reach of glutinous corn-based MSME products. Keywords : glutinous corn, msmes, training, processed products